1988
DOI: 10.1159/000153768
|View full text |Cite
|
Sign up to set email alerts
|

The Le(a+b+) Phenotype in Polynesians

Abstract: The presence of the rare Lewis phenotype Le(a+b+) is reported in various Polynesian groups, including Maoris, Samoans, Cook Islanders, Nuieans and Tokelau Islanders. The phenotype was found in Polynesians of all blood groups and the frequency was significantly increased in group 0 persons. The phenotype was not significantly associated with H reactivity in group A donors and showed no correlation with age or sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…The results of our study together with those of Henry et al [3] appear to indicate that the Le(a+b+) phenotype is almost ex clusive to populations of southeast Asia.…”
Section: Introductionsupporting
confidence: 86%
“…The results of our study together with those of Henry et al [3] appear to indicate that the Le(a+b+) phenotype is almost ex clusive to populations of southeast Asia.…”
Section: Introductionsupporting
confidence: 86%
“…As participants of the 1990 workshop we used the monoclonal Lewis reagents supplied to further investigate the unusual phenotypes found in Polynesians [10,15,16], Previous results had suggested that there may be an Leb epitope common to all Polynesian Le(a-b+) individuals but not common to all Le(a+b+) individuals [15].…”
Section: Discussionmentioning
confidence: 99%
“…It was anticipated that if a weak secretor gene was present, it would result in reduced levels of ABH secretory substances. As group A persons exhibit the Le(a+b+) phenotype less frequently than group O individuals [3], the finding of group A Le(a-l-b-) red cells unable to express detectable Leb antigen, but with salivary ABH substances present would be expected.…”
Section: Introductionmentioning
confidence: 95%
“…Carefully controlled trials to determine the type and dilution of antisera that was able to define partial secretion of ABH substances were necessary [5,6]. Red cell and salivary ABH and Lewis phenotypes were deter mined in order to establish the existence of weak secretor phenotypes.…”
mentioning
confidence: 99%